Representation of Biracial Identity in Mariah Carey’s Songs: Literary and Cultural Perspectives - Boli, Hubertus Ade Resha Raditya (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2025)
The concept of biracial identity has gained attention in cultural studies, particularly in a globalized world where racial boundaries are increasingly fluid. However, there is limited research on its representation in music. While visual and narrative arts often dominate such studies, music’s lyrical storytelling remains underexplored. This study addresses the gap by analyzing biracial identity in Mariah Carey’s songs “Outside”, “Petals”, and “Close My Eyes”. Using Stuart Hall’s Representation Theory and Critical Race Theory (CRT), it examines how her lyrics explore societal alienation, identity conflict, and self-acceptance. The findings reveal Carey’s music as both personal narrative and cultural critique, challenging systemic racism and societal norms. Her work highlights identity’s fluidity and amplifies marginalized voices, illustrating music’s potential to address social issues. This research underscores the importance of inclusive representation in promoting diversity and contributing to discourses on race, identity, and belonging.